Effect of intraocular pressure on crystalline lens oscillations: a computational study using porcine eye model - Ali Dahaghin; Milad Salimibani; Agnieszka Boszczyk; Jorge Grasa; Damian Siedlecki (PLoS ONE, 2025)
This study addresses a crucial knowledge gap by investigating the impact of intraocular pressure (IOP) on the wobbling characteristics of the crystalline lens in an ex vivo setting. It utilizes previous validated computational porcine eye models, which offer anatomical and physiological similarities to the human eye. These models incorporate fluid-structure interaction (FSI) to simulate the mechanical interaction between the fluids of the eye and the solid structures. Simulations were conducted under constant mechanical properties and boundary conditions, allowing for precise quantification of lens wobbling behavior with varying IOP levels. Various trends in lens displacement were observed at various IOP levels, revealing significant variations in both magnitude and duration. The results demonstrate the central role of intraocular pressure in influencing lens overshooting during rotational motion, with potential clinical implications. The observed lens displacement patterns, particularly in conditions like glaucoma, underscore the importance of considering IOP as a critical factor in understanding ocular biomechanics. Beyond immediate biomechanical relevance, the study’s findings suggest the potential use of the Purkinje imaging system as a non-invasive method for IOP estimation based on lens overshoot as an “inverse solution” strategy. This non-invasive imaging technique offers a promising alternative to traditional methods, minimizing patient discomfort and potentially enhancing measurement precision.